2001
DOI: 10.1053/jhep.2001.29400
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of I[kappa ]B superrepressor gene with adenovirus reduces early alcohol-induced liver injury in rats

Abstract: Chronic alcohol administration increases gut-derived endotoxin in the portal blood, which activates Kupffer cells through nuclear factor B (NF-B) to produce toxic mediators such as proinflammatory cytokines, leading to liver injury. Therefore, a long-term intragastric ethanol feeding protocol was used here to test the hypothesis that NF-B inhibition would prevent early alcohol-induced liver injury. Adenoviral vectors encoding either the transgene for IB superrepressor (AdIB-SR) or the bacterial ␤-galactosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 42 publications
3
50
0
1
Order By: Relevance
“…26,29) It has been reported that it would be highly desirable to develop a pharmacological strategy to suppress the activation of NF-κB. 30,31) In the present work, gomisin A remarkably suppressed p-IκB and NF-κB expression following acute liver injury. This is the first report to show that gomisin A inhibited the activation of NF-κB, which may be associated with a reduction in the phosphorylation of IκB.…”
Section: Discussionsupporting
confidence: 50%
“…26,29) It has been reported that it would be highly desirable to develop a pharmacological strategy to suppress the activation of NF-κB. 30,31) In the present work, gomisin A remarkably suppressed p-IκB and NF-κB expression following acute liver injury. This is the first report to show that gomisin A inhibited the activation of NF-κB, which may be associated with a reduction in the phosphorylation of IκB.…”
Section: Discussionsupporting
confidence: 50%
“…Endotoxin activates NF-kB, leading to the hypothesis that inhibition of NF-kB in Kupffer cells would prevent ALD [90]. Administration of an adenovirus encoding for the IkB superrepressor to rats chronically infused with ethanol blunted the ethanol-induced activation of NF-kB, TNFa production, and pathological changes.…”
Section: Kupffer Cells and Alcoholic Liver Diseasementioning
confidence: 99%
“…Some reports have indicated that hepatic injury induced by ischemia-reperfusion, alcohol, or endotoxin can be ameliorated by suppressing NF-B activation in the liver, especially in liver macrophages (14,33,35,36). However, whether selective and direct inactivation of NF-B in liver macrophages can suppress CCl 4 -induced liver injury or fibrosis has been unclear so far, whereas nonspecific inactivation of hepatic NF-B by some NF-B inhibitors has been reported to be antifibrogenic (6,26).…”
mentioning
confidence: 99%